Prevalence and Risk Factors of Repeat Breeding in Commercial Dairy Farms of Chittagong District of Bangladesh - Nath, BK; Das, BC; Bari, MS; Rahman, MA (International Journal of Natural Sciences, 2016)
The study was conducted to measure the prevalence of repeat breeding cows and to identify the potential risk factors of Repeat breeding syndrome in commercial dairy farms at Chittagong of Bangladesh during July 2011 to October 2012. A total of 15 government registered dairy farms having 283 cows were surveyed for individual and farm level variables identified using preset questionnaire. Out of them 56 dairy cows was sampled for bacteriological exploration and culture sensitivity test. Overall prevalence of repeat breeder cow in commercial dairying of Chittagong was 11.3%. The univariate analysis screened potential cow level exposure high yielding cows (p=0.02) and cows having peripartum events (dystocia) in last calving (p=0.001). Among farm level exposures, owner educational level (p=0.05), nature of feed offer at farm (p=0.06) were evident to be potential screened factors for repeat breeding. From the 32 repeat breeders, Staphylococcus spp. 13 (40.6%) was isolated as predominant bacteria followed by Escherichia coli 8 (25%), Bacillus spp 6 (18.8%), Corynebacterium spp 6 (18.8%) and Pseudomonas spp 5 (15.6%). The isolates of bacteria were more or less effective against eight antibiotic agents. Gentamicin 36 (97.3%) showed higher sensitivity followed by ceftriaxone 33 (89.2%), chloramphenicol 33 (89.2%) indicates the effectiveness of these antibiotics in treating repeat breeding. Moreover, the identified potential risk factors should be controlled to minimize the economic loss of dairy farms. International Journal of Natural Sciences (2014), 4(1) 21-27